Soccer under the Swastika : stories of survival and resistance during the Holocaust - Simpson, Kevin E. (Rowman and Littlefield, 2016)
As millions were caught up in the conflict of World War II, soccer emerged as both a response to domination and a means of manipulation by those in power. Soccer under the Swastika reveals this little-known part of history, rescuing from obscurity many poignant survivor testimonies, old accounts of wartime players, and the diaries of survivors and perpetrators. In victim accounts and rare photographs-many published for the first time in this book-hidden stories of soccer in almost every Nazi concentration camp appear. To these captives, soccer was a means of survival, a glimmer of joy between.